2022
DOI: 10.3389/fmolb.2022.842582
|View full text |Cite
|
Sign up to set email alerts
|

Linking Alzheimer’s Disease and Type 2 Diabetes: Characterization and Inhibition of Cytotoxic Aβ and IAPP Hetero-Aggregates

Abstract: The cytotoxic self-aggregation of β-amyloid (Aβ) peptide and islet amyloid polypeptide (IAPP) is implicated in the pathogenesis of Alzheimer’s disease (AD) and Type 2 diabetes (T2D), respectively. Increasing evidence, particularly the co-deposition of Aβ and IAPP in both brain and pancreatic tissues, suggests that Aβ and IAPP cross-interaction may be responsible for a pathological link between AD and T2D. Here, we examined the nature of IAPP-Aβ40 co-aggregation and its inhibition by small molecules. In specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 126 publications
1
18
0
Order By: Relevance
“…Since the cyclic peptide alone did not generate any detectable CD signal, the enhancement of the CD signal may be attributed to the interaction of Aβ42 with the cyclic peptide. The calculated sum of the CD ellipticity values of the spectra of the cyclic peptide and Aβ42 differed from the spectrum obtained for the Aβ42/cyclic peptide mixture, indicating the existence of interactions between Aβ42 and the cyclic peptide (a method of analysis described in previous reports). Importantly, the formation of the β-sheet structure in freshly dissolved Aβ42 in the presence of the cyclic peptide was detected immediately upon addition of the cyclic peptide to the Aβ42 solution (i.e., at incubation time 0), whereas Aβ42 alone showed a predominantly random structure with a typical minimum at 197 nm (Figure S5A). , Here again, the calculated sum of the individual spectra of Aβ42 and the cyclic peptide (when measured separately) differed from the CD spectrum that was obtained for the mixture, indicating that Aβ42-cyclic peptide interactions occurred immediately upon mixing the peptides.…”
Section: Resultsmentioning
confidence: 88%
“…Since the cyclic peptide alone did not generate any detectable CD signal, the enhancement of the CD signal may be attributed to the interaction of Aβ42 with the cyclic peptide. The calculated sum of the CD ellipticity values of the spectra of the cyclic peptide and Aβ42 differed from the spectrum obtained for the Aβ42/cyclic peptide mixture, indicating the existence of interactions between Aβ42 and the cyclic peptide (a method of analysis described in previous reports). Importantly, the formation of the β-sheet structure in freshly dissolved Aβ42 in the presence of the cyclic peptide was detected immediately upon addition of the cyclic peptide to the Aβ42 solution (i.e., at incubation time 0), whereas Aβ42 alone showed a predominantly random structure with a typical minimum at 197 nm (Figure S5A). , Here again, the calculated sum of the individual spectra of Aβ42 and the cyclic peptide (when measured separately) differed from the CD spectrum that was obtained for the mixture, indicating that Aβ42-cyclic peptide interactions occurred immediately upon mixing the peptides.…”
Section: Resultsmentioning
confidence: 88%
“…According to the above results, it can be concluded that the cross−interaction between the PSMα3 monomer and the Aβ 40 monomer resulted in the formation of non−fibrillar heterogeneous aggregates (Figure 1c), similar to the hetero−oligomers formed by Aβ and human islet amyloid polypeptide (hIAPP) [39,40] or tau [41]. These heterogeneous structures interfered with the conformational transitions of Aβ 40 , resulting in reduced ThT fluorescence (Figure 1a).…”
Section: Effects Of the Psmα3 Monomer On Aβ 40 Aggregationmentioning
confidence: 91%
“…Cerebrovascular abnormalities such as haemorrhagic infarcts, minor and large ischemic cortical infarcts, vasculopathies, and changes in cerebral white matter have all been linked to an increased risk of dementia. Post-mortem examinations of the brains of Alzheimer's disease patients reveal the existence of parenchymal vascular disease (amyloid angiopathy by Aβ peptide and small channel arteriolosclerosis illness), with haemorrhagic breakouts and infarcts observed in more than half of them [143][144]. According to neuropathological results, between 6 to 47 percent of those with dementia have cerebrovascular disease.…”
Section: Cerebrovascular Diseasesmentioning
confidence: 99%